Does Affinity Country Really Matter? Re-examining the Effect of Consumer Affinity on Consumer Purchase Intention - Zaid Zaid; Katon Pratondo; Anggraeni Pratama Indrianto; Ikhsan Nurahman (International Journal of Social Science and Business, 2022)
Nowadays consumer affinity regularly has an important role and a positive effect on the purchase intention of products made in affinity countries. This study aims to analyses the effect of consumer affinity on purchase intention by involving product trust as a mediating variable. This study is a quantitative study with a cross-sectional survey approach. This study are involving 311 respondents as the subject. The data collected uing questionnaire and then processed using the partial least squares structural equation modeling (PLS-SEM) method to evaluate the effect of consumer affinity and product trust on purchase intention. The results of this study reveal that consumer affinity has a negative effect on purchase intention but has a positive effect on product trust. Meanwhile, product trust has a direct and positive effect on purchase intention. This study also analyses the indirect effect of consumer affinity on purchase intention through product trust and the results show that product trust is proven to mediate the effect of consumer affinity on purchase intention.